A systematic review and meta-analysis on abnormal posturing among brain injury patients - Wei, Yuyu; Cui, Yan; Pang, Xiaojun; Wang, Weijie (Arquivos de Neuro-Psiquiatria, 2024)
Background Abnormal motor posturing (AMP), exhibiting as decorticate, decerebrate, or opisthotonos, is regularly noticed among children and adults.Objective This systematic review and meta-analysis examined the risk factors and outcome of posturing among severe head and brain injury subjects.Methods Based on the inclusion and exclusion criteria and using MeSH terms: “decerebrate posturing”, “opisthotonic posturing”, “brain injury”, and/or “cerebral injury” articles were searched on Scopus, PubMed, Science Direct, and google scholar databases. Observational studies, case series, and case reports were included.Results A total of 1953 studies were retrieved initially, and based on the selection criteria, 20 studies were finally selected for review and were analyzed for meta-analysis based on the mortality between the hematomas. The functional outcomes of this study are the risk factors, mortality rate and Glasgow Outcome Scale. Decerebrative patients were higher among the studies related to head injury surgeries. Males were mainly treated for decerebrate postures compared with the female subjects. Extradural hematoma and acute subdural hematoma with cerebral contusion were quite common in the surgical mass lesions.Conclusion The findings reported that the lesion types, the operative procedures, and the age of the decerebrating patients with brain injuries are the significant prognostic factors determining the survival outcomes.
Keywords: Decerebrate State; Brain Injuries; Systematic Review; Brain Injuries